The Urgency of Guidance in Correctional Institutions - Muhammad Akbar Fhad Syahril; Ibrahim Rusli2, Ibrahim Rusli; Ardyanti Aris (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to determine and analyze the implementation of prisoner coaching. This research uses normative and empirical research. Normative and empirical variety research is used in this study. Normative research examines laws, ideas, and conceptions related to the problem being investigated. The field as the primary data source includes findings from interviews and observations. Which is supported by a statutory approach and an analytical approach. The results of the study indicate that the implementation of coaching has not been effective, when viewed from the understanding of the existing guidance in the detention center, there are still obstacles in the implementation of coaching, the number of inmates who are not following the capacity (over-capacity), lack of facilities and infrastructure for coaching and health services.